Effect of polyvinylpyrrolidone additive in the substrate of thin-film composite forward osmosis polyvinylidene fluoride membrane on neodymium rejection - Yeoh, Yuan Xin; Mazrul Nizam, Abu Seman; Mohd Yusri, Mohd Yunus; Abdul Wahab, Mohammad; Nurul Ain, Ismail (Elsevier Ltd, 2025)
Green technology has become the research focus in many developed countries to reduce carbon emissions. Green technology innovations, especially green energy require a strong permanent magnet that utilizes rare earth elements (REE) such as neodymium (Nd) as raw materials. Direct mining of REE from primary sources and downstream recycling process from secondary resources are infeasible due to the pollution caused by strong acid used in the cracking and leaching process. Hence, this study proposes the utilization of acid mine drainage (AMD) produced from upstream and midstream processes using forward osmosis (FO) to concentrate Nd. A synthetic AMD containing Nd was used in the experimental work. Dope solutions were prepared from 17 wt% polyvinylidene fluoride (PVDF) and different polyvinylpyrrolidone (PVP) concentrations as pore-forming agents. Then, the non-solvent induced phase separation (NIPS) method was used to cast the substrate and the interfacial polymerization (IP) process was applied to form a polyamide (PA) thin-film active layer on the top surface. All TFC membranes except pristine PVDF membranes were able to reject neodymium higher than 94 %. TFC membrane substrate prepared using 10 wt% PVP exhibited the highest Nd rejection efficiency with 99.15 % which can be justified by the low B value indicating the membrane prevented the permeation of Nd. The FESEM result indicated no PA layer was formed on the pristine PVDF substrate, and it was confirmed by the FTIR spectra. This study revealed that PVP is a crucial additive in the preparation of the TFC FO membrane for the Nd rejection in AMD.